Kajian Teoritis tentang Konstruksi Manajemen Lembaga Pendidikan Islam - Murodah, Nelli (Sekolah Tinggi Agama Islam (STAI) Ki Ageng Pekalongan, Indonesia, 2024)
This research aims to describe the theoretical construction of the management of Islamic educational institutions. This qualitative research is a library study with a qualitative descriptive approach. The research data uses references from various scientific literature that has close relevance to the subject matter of the research. Then, the stages of reduction, presentation, and conclusion drawing are used as data analysis techniques. The results concluded that there are five fundamental aspects in the construction of the management of Islamic educational institutions which include the management of personnel, students, curriculum, finance, and pre-facilities. The five managements are expected to work synergistically, so that it is expected to build a good Islamic education institution management construction. This research contributes to the urgency of a systemic and measurable management strategy of Islamic educational institutions.